THE ROLE OF PROCEDURAL JUSTICE THEORY IN PARTICIPATIVE BUDGETING AND ITS IMPACT ON JOB PERFORMANCE AND JOB SATISFACTION MODERATED BY CULTURAL DIMENSION: A LITERATURE REVIEW - SLAMET SUGIRI; NASUHI HIDAJAT (Jurnal Bisnis dan Akuntansi, 2003)
In this paper we review the motions of participative budgeting, procedural justice, cultural dimensions, and job performance as well as job satisfaction. We learn from this review that previous find inconsistent findings on the relationship between participative budgeting and job performance and job satisfaction. Most studies focus on the consequences rather than the antecedents of participative budgeting. We also learn from reviewing the extant theories on participative budgeting that empirical studies on the relationship between participative budgeting and job performance and job satisfaction use a procedural justice concept as the underlying theory. Since the procedural justice, viewed from psychological standpoint, is one of the antecedents to participative budgeting, we posit that the inconsistent findings aforementioned are caused by lack of attention to the antecedents of budgetary participation. Different cultures among nations may also cause different effects of participation. Different cultures among nations may also cause different effects of participative budgeting on job performance and job satisfaction. Thus, we still have a good room to conduct empirical studies to confirm whether procedural justice can enhance the association of participative budgeting with job performance and job satisfaction, especially using subjects from nations that possess different culture from American.